2011
DOI: 10.1182/blood-2010-10-314518
|View full text |Cite
|
Sign up to set email alerts
|

The genome of self-complementary adeno-associated viral vectors increases Toll-like receptor 9–dependent innate immune responses in the liver

Abstract: IntroductionAdeno-associated viral (AAV) vectors are widely used for stable in vivo gene transfer to terminally differentiated or quiescent cells such as muscle fibers, hepatocytes, neurons, retinal cells, and others. These vectors, derived from a nonpathogenic, replicationdefective parvovirus with a small single-stranded (ss) DNA genome, have recently been successfully used in clinical gene transfer for inherited blindness and also show promise for other diseases. 1,2 Eight years ago, Zaiss et al 3 found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
244
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(262 citation statements)
references
References 50 publications
(65 reference statements)
18
244
0
Order By: Relevance
“…Both type I and II interferons have been shown to increase in mice treated with AAV vectors; increases in IFN-a may be upregulated by AAV after activation of Toll-like receptor-9 (TLR9) in response to intracellular viral genomes, while increases in IFN-c appear to be associated with activated T cells. 37 In this study, there was no evidence of an IFN-a or IFN-c response in restimulated PBMCs, serum, or synovial fluid at any time point. In addition, no significant increases in IL-6 or IL-10 were seen after rAAV2 or rAAV5 administration.…”
Section: Discussionmentioning
confidence: 47%
“…Both type I and II interferons have been shown to increase in mice treated with AAV vectors; increases in IFN-a may be upregulated by AAV after activation of Toll-like receptor-9 (TLR9) in response to intracellular viral genomes, while increases in IFN-c appear to be associated with activated T cells. 37 In this study, there was no evidence of an IFN-a or IFN-c response in restimulated PBMCs, serum, or synovial fluid at any time point. In addition, no significant increases in IL-6 or IL-10 were seen after rAAV2 or rAAV5 administration.…”
Section: Discussionmentioning
confidence: 47%
“…TLR9 has been implicated as a mediator of immunoreactivity toward single-stranded and self-complementary AAVs (scAAVs) due to its ability to recognize unmethylated CpG motifs present in the therapeutic expression cassettes packaged in an AAV capsid (15). Zhu et al demonstrated the role of TLR9/MyD88 signaling in mouse plasmacytoid dendritic cells as an important mediator of…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TLR9 has the potential to recognize unmethylated CpG motifs in the therapeutic expression cassettes packaged in an AAV capsid and induce innate and adaptive immunity (15). Previous reports revealed that innate immune recognition of the serotype AAV2 by plasmacytoid dendritic cells was mediated by TLR9 and dependent on MyD88 signaling, independent of the form of transgene (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their DNA genome and capsid structure is being sensed by Toll-like receptors 9 and 2, respectively, and humans often have preexisting immunity. [8][9][10][11][12][13] Activation of capsid-specific CD8…”
Section: Introductionmentioning
confidence: 99%